Silicone terpolymers and methods for making the same
Patent Information
- Application Number
- CN202611103680.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
聚二甲基硅氧烷虽然具有较好的链段柔顺性和亲有机特性,但在非极性或弱极性有机溶剂中容易发生明显溶胀,导致制备的膜层尺寸稳定性、选择性保持能力和长期运行稳定性不足
[0009]本公开的上述各个实施例具有如下有益效果:通过本公开的一些实施例的硅氧烷三元共聚物,可以在低表面能、耐溶剂溶胀性、疏水亲有机性和加工成膜性之间取得较好的平衡,适合作为渗透汽化复合膜选择性分离层的基础聚合物,有利于提升硅氧烷材料在有机溶剂分离、共沸体系分离及高稳定性膜材料领域中的应用适应性。具体来说,造成在低表面能、耐溶剂溶胀性、疏水亲有机性和加工成膜性之间难以较好平衡,硅氧烷材料在有机溶剂分离、共沸体系分离及高稳定性膜材料领域中的应用适应性较差的原因在于:聚二甲基硅氧烷虽然具有较好的链段柔顺性和亲有机特性,但在非极性或弱极性有机溶剂中容易发生明显溶胀,导致制备的膜层尺寸稳定性、选择性保持能力和长期运行稳定性不足。含氟硅氧烷结构单元能够降低材料表面能并改善耐溶剂性,但单纯引入含氟侧基时,聚合物与部分有机相之间的相容性和成膜加工适应性仍有一定限制;长链烷基侧基有利于增强疏水亲有机特性和有机相相容性,但若缺少含氟结构单元的协同调控,又难以有效抑制有机溶剂引起的过度溶胀,造成制备膜的效果较差;现有二元硅氧烷共聚物通常侧重于单一性能提升,难以同时兼顾低表面能、耐溶剂溶胀性、亲有机相容性和后续交联成膜能力,造成使用的效果较差。基于此,本公开的一些实施例的硅氧烷三元共聚物包括聚硅氧烷主链以及位于上述聚硅氧烷主链两端的二甲基乙烯基硅基端基;上述聚硅氧烷主链由二甲基硅氧烷结构单元、甲基(3,3,3-三氟丙基)硅氧烷结构单元和甲基辛基硅氧烷结构单元无规共聚形成;以上述二甲基硅氧烷结构单元、上述甲基(3,3,3-三氟丙基)硅氧烷结构单元和上述甲基辛基硅氧烷结构单元的总摩尔量为100%计,上述二甲基硅氧烷结构单元的含量为40~90mol%,上述甲基(3,3,3-三氟丙基)硅氧烷结构单元的含量为5~35mol%,上述甲基辛基硅氧烷结构单元的含量为5~25mol%;上述硅氧烷三元共聚物的数均分子量Mn为40000~180000g/mol;上述硅氧烷三元共聚物的分子量分布指数处于的范围为1.7~2.4。也因为引入了甲基(3,3,3-三氟丙基)硅氧烷结构单元,其表面能可降至15mN/m以下,而非传统PDMS的22mN/m左右,由此弥补了传统PDMS分子间作用力弱、缺乏低表面能功能基团的缺陷,进而改善其耐非极性溶剂溶胀性,使其可适配苛刻油性环境及极端疏油应用。还因为同步引入了甲基辛基硅氧烷结构单元,而非仅保留PDMS单一分子结构,所以有效改善了聚合物与多种有机溶剂的相容性,打破了其在溶剂分离等领域的应用限制。又因为该三元共聚物并非仅引入一种功能改性基团,而是同时整合氟基团与长链烷基的优势,实现了超低表面能、优异耐溶剂性与良好有机相容性的协同提升,克服了现有二元共聚物的短板。与聚二甲基硅氧烷相比,所制备的硅氧烷三元共聚物在保持良好成膜性和链段柔顺性的基础上,能够降低聚合物在有机溶剂中的过度溶胀倾向,提高材料在高浓度有机溶剂或长周期溶剂分离环境中的尺寸稳定性和性能保持能力。与单纯含氟硅氧烷聚合物相比,甲基辛基硅氧烷结构单元的引入有利于改善聚合物与有机相之间的相容性,提升后续涂覆和交联成膜过程中的加工适应性。通过八甲基环四硅氧烷、1,3,5-三甲基-1,3,5-三(3,3,3-三氟丙基)环三硅氧烷和四甲基四辛基环四硅氧烷的开环共聚,并配合乙烯基封端剂调控分子量和端基结构,能够在较温和条件下制备具有特定组成范围、分子量范围和分子量分布的硅氧烷三元共聚物。该方法有利于实现含氟侧基和长链烷基侧基在同一聚硅氧烷主链中的协同引入,克服现有二元硅氧烷共聚物难以同时兼顾耐溶剂性、亲有机性、组成可调性和后续交联成膜适应性的不足。由此,可以在低表面能、耐溶剂溶胀性、疏水亲有机性和加工成膜性之间取得较好的平衡,适合作为渗透汽化复合膜选择性分离层的基础聚合物,有利于提升硅氧烷材料在有机溶剂分离、共沸体系分离及高稳定性膜材料领域中的应用适应性。
Smart Images

Figure CN122978449A_ABST
Abstract
Description
Technical Field
[0001] The embodiments disclosed herein relate to the field of polymer materials technology, specifically to siloxane terpolymers and their preparation methods. Background Technology
[0002] Polydimethylsiloxane (PDS) has been widely used in membrane separation applications such as pervaporation, organic vapor separation, and solvent separation due to its flexible siloxane backbone, low glass transition temperature, and good film-forming properties. Currently, high-performance siloxane separation membrane materials are typically based on PDS or its binary modified copolymers, and their solubility selectivity, permeate flux, and operational stability are improved by adjusting the side group structure, crosslinking density, or composite membrane structure.
[0003] However, in practice, it has been found that when polydimethylsiloxane is used as a high-performance separation membrane material, the following technical problems often arise: While polydimethylsiloxanes possess good segmental flexibility and organophilic properties, they are prone to significant swelling in nonpolar or weakly polar organic solvents, leading to insufficient dimensional stability, selectivity retention, and long-term operational stability of the prepared films. Fluorinated siloxane structural units can reduce surface energy and improve solvent resistance, but simply introducing fluorinated side groups still limits the compatibility between the polymer and some organic phases, as well as the adaptability to film formation. Long-chain alkyl side groups are beneficial for enhancing hydrophobic-organophilic properties and organic phase compatibility, but without the synergistic regulation of fluorinated structural units, it is difficult to effectively suppress excessive swelling caused by organic solvents, resulting in poor film preparation performance. Existing binary siloxane copolymers typically focus on improving a single property, making it difficult to simultaneously achieve low surface energy, solvent swelling resistance, organophilic compatibility, and subsequent crosslinking film formation ability, resulting in poor performance in use.
[0004] The information disclosed in this background section is only intended to enhance the understanding of the background of the inventive concept, and therefore may contain information that does not form prior art known to those skilled in the art. Summary of the Invention
[0005] The summary portion of this disclosure is intended to provide a brief overview of the concepts, which will be described in detail in the detailed description portion. This summary portion is not intended to identify key or essential features of the claimed technical solutions, nor is it intended to limit the scope of the claimed technical solutions.
[0006] Some embodiments of this disclosure provide siloxane terpolymers and their preparation methods to address one or more of the technical problems mentioned in the background section above.
[0007] In a first aspect, some embodiments of this disclosure provide a siloxane terpolymer, characterized in that the siloxane terpolymer comprises a polysiloxane backbone and dimethylvinylsilyl end groups located at both ends of the polysiloxane backbone; the polysiloxane backbone is formed by random copolymerization of dimethylsiloxane structural units, methyl (3,3,3-trifluoropropyl)siloxane structural units, and methyl octylsiloxane structural units; based on the total molar amount of the dimethylsiloxane structural units, the methyl (3,3,3-trifluoropropyl)siloxane structural units, and the methyl octylsiloxane structural units being 100%, the content of the dimethylsiloxane structural units is 40-90 mol%, the content of the methyl (3,3,3-trifluoropropyl)siloxane structural units is 5-35 mol%, and the content of the methyl octylsiloxane structural units is 5-25 mol%; the number average molecular weight M of the siloxane terpolymer is... n The molecular weight distribution index of the above-mentioned siloxane terpolymer is 40,000~180,000 g / mol; the molecular weight distribution index of the above-mentioned siloxane terpolymer is in the range of 1.7~2.4.
[0008] Secondly, some embodiments of this disclosure provide a method for preparing a siloxane terpolymer. This method is used to prepare the siloxane terpolymer as described in the first aspect above, comprising: preparing a monomer mixture containing octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane under inert gas protection and anhydrous conditions; controlling the temperature of the monomer mixture to 50-65°C; adding a catalyst; and performing a ring-opening polymerization reaction to obtain a polymerization reaction solution; and adding tetramethylcyclotetrasiloxane to the polymerization reaction solution. Divinyldisiloxane undergoes an end-capping reaction to obtain a capped reaction solution; the capped reaction solution is cooled to obtain a cooled reaction solution; a quenching agent is added to the cooled reaction solution to quench it, resulting in a quenched reaction solution; the quenched reaction solution is washed with water until the aqueous phase is neutral, and the organic phase is separated; the organic phase is subjected to vacuum degassing to remove volatiles, resulting in a siloxane terpolymer, wherein the siloxane terpolymer is an α,ω-divinyl-capped poly(dimethylsiloxane-co-methyl(3,3,3-trifluoropropyl)siloxane-co-methyloctylsiloxane).
[0009] The above-described embodiments of this disclosure have the following beneficial effects: the siloxane terpolymers of some embodiments of this disclosure can achieve a good balance between low surface energy, solvent swelling resistance, hydrophobic-organophilic properties, and processability for film formation, making them suitable as the base polymer for the selective separation layer of pervaporation composite membranes. This is beneficial for improving the application adaptability of siloxane materials in the fields of organic solvent separation, azeotropic system separation, and high-stability membrane materials. Specifically, the reason why it is difficult to achieve a good balance between low surface energy, solvent swelling resistance, hydrophobic-organophilic properties, and processability for film formation, and why siloxane materials have poor application adaptability in the fields of organic solvent separation, azeotropic system separation, and high-stability membrane materials, is that although polydimethylsiloxane has good segmental flexibility and organic affinity, it is prone to significant swelling in non-polar or weakly polar organic solvents, resulting in insufficient dimensional stability, selectivity retention, and long-term operational stability of the prepared membrane layer. Fluorinated siloxane structural units can reduce the surface energy of materials and improve solvent resistance, but when fluorinated side groups are introduced alone, the compatibility between the polymer and some organic phases and the adaptability of film formation processing are still limited. Long-chain alkyl side groups are beneficial to enhance hydrophobic and organic-friendly properties and organic phase compatibility, but without the synergistic regulation of fluorinated structural units, it is difficult to effectively suppress excessive swelling caused by organic solvents, resulting in poor film preparation performance. Existing binary siloxane copolymers usually focus on improving a single property, and it is difficult to simultaneously achieve low surface energy, solvent swelling resistance, organic-friendly compatibility and subsequent crosslinking film formation ability, resulting in poor performance in use. Based on this, some embodiments of the siloxane terpolymer of this disclosure include a polysiloxane backbone and dimethylvinylsilyl end groups located at both ends of the polysiloxane backbone; the polysiloxane backbone is formed by random copolymerization of dimethylsiloxane structural units, methyl (3,3,3-trifluoropropyl)siloxane structural units and methyl octylsiloxane structural units; based on the total molar amount of the dimethylsiloxane structural units, the methyl (3,3,3-trifluoropropyl)siloxane structural units and the methyl octylsiloxane structural units being 100%, the content of the dimethylsiloxane structural units is 40-90 mol%, the content of the methyl (3,3,3-trifluoropropyl)siloxane structural units is 5-35 mol%, and the content of the methyl octylsiloxane structural units is 5-25 mol%; the number average molecular weight M of the siloxane terpolymer is... nThe molecular weight distribution index (MDI) of the aforementioned siloxane terpolymer ranges from 40,000 to 180,000 g / mol, and from 1.7 to 2.4. Due to the introduction of methyl (3,3,3-trifluoropropyl)siloxane structural units, its surface energy can be reduced to below 15 mN / m, instead of the approximately 22 mN / m of traditional PDMS. This compensates for the weak intermolecular forces and lack of low-surface-energy functional groups in traditional PDMS, thereby improving its resistance to swelling in non-polar solvents and making it suitable for harsh oily environments and extremely oleophobic applications. Furthermore, the simultaneous introduction of methyl octylsiloxane structural units, rather than retaining only the single PDMS molecular structure, effectively improves the polymer's compatibility with various organic solvents, breaking its application limitations in solvent separation and other fields. Moreover, because this terpolymer does not only introduce one functional modifying group but also integrates the advantages of fluorine groups and long-chain alkyl groups, it achieves a synergistic improvement in ultra-low surface energy, excellent solvent resistance, and good organic compatibility, overcoming the shortcomings of existing binary copolymers. Compared to polydimethylsiloxane, the prepared siloxane terpolymers, while maintaining good film-forming properties and chain segment flexibility, can reduce the excessive swelling tendency of the polymer in organic solvents and improve the dimensional stability and performance retention of the material in high-concentration organic solvents or long-term solvent separation environments. Compared with pure fluorinated siloxane polymers, the introduction of methyl octylsiloxane structural units is beneficial to improving the compatibility between the polymer and the organic phase, and enhancing the processing adaptability in subsequent coating and crosslinking film formation processes. Through ring-opening copolymerization of octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane, and by using vinyl end-capping agents to regulate molecular weight and end-group structure, siloxane terpolymers with specific compositional ranges, molecular weight ranges, and molecular weight distributions can be prepared under relatively mild conditions. This method facilitates the synergistic introduction of fluorinated side groups and long-chain alkyl side groups into the same polysiloxane backbone, overcoming the shortcomings of existing binary siloxane copolymers that struggle to simultaneously achieve solvent resistance, organophilicity, compositional tunability, and adaptability for subsequent crosslinking and film formation. Consequently, a better balance can be achieved between low surface energy, solvent swelling resistance, hydrophobicity and organophilicity, and processability for film formation. This makes it suitable as a base polymer for the selective separation layer of pervaporation composite membranes, enhancing the application adaptability of siloxane materials in organic solvent separation, azeotropic system separation, and high-stability membrane materials. Attached Figure Description
[0010] The above and other features, advantages, and aspects of the embodiments of this disclosure will become more apparent from the accompanying drawings and the following detailed description. Throughout the drawings, the same or similar reference numerals denote the same or similar elements. It should be understood that the drawings are schematic, and elements are not necessarily drawn to scale.
[0011] Figure 1This is a flowchart of some embodiments of the method for preparing siloxane terpolymers according to this disclosure; Figure 2 The Fourier transform infrared (FT-IR) spectrum of the terpolymer synthesized according to Example 1 of the siloxane terpolymer and its preparation method disclosed herein; Figure 3 The 1H NMR spectrum of the terpolymer synthesized according to Example 1 of the siloxane terpolymer and its preparation method disclosed herein is shown. 1 H-NMR spectrum; Figure 4 This is a comparison chart of the water contact angle test results of the products of Comparative Example 1 (fluorine-free) and Example 1, based on the siloxane terpolymer and its preparation method disclosed herein. Figure 5 This is a physical image of a siloxane terpolymer prepared according to the siloxane terpolymer and its preparation method disclosed herein, used for internal testing. Figure 6 It is based on the structural formula of tetramethyltetraoctylcyclotetrasiloxane in the siloxane terpolymer and its preparation method disclosed herein; Figure 7 It is based on the structural formula of octamethylcyclotetrasiloxane in the siloxane terpolymer and its preparation method disclosed herein; Figure 8 It is based on the structural formula of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane in the siloxane terpolymer and its preparation method disclosed herein; Figure 9 It is based on the structural formula of trifluoromethanesulfonic acid in the siloxane terpolymer and its preparation method disclosed herein; Figure 10 It is based on the structural formula of the end-capping agent in the siloxane terpolymer and its preparation method disclosed herein; Figure 11 It is based on the structural formula of the siloxane terpolymer and its preparation method disclosed herein; Figure 12 This is a schematic diagram of the synthesis process of the siloxane terpolymer according to the present disclosure and its preparation method. Detailed Implementation
[0012] Embodiments of this disclosure will now be described in more detail with reference to the accompanying drawings. While some embodiments of this disclosure are shown in the drawings, it should be understood that this disclosure can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of this disclosure. It should be understood that the accompanying drawings and embodiments of this disclosure are for illustrative purposes only and are not intended to limit the scope of protection of this disclosure.
[0013] It should also be noted that, for ease of description, only the parts relevant to the invention are shown in the accompanying drawings. Unless otherwise specified, the embodiments and features described in this disclosure can be combined with each other.
[0014] It should be noted that the concepts of "first" and "second" mentioned in this disclosure are used only to distinguish different devices, page modules or units, and are not used to limit the order or interdependence of the functions performed by these devices, page modules or units.
[0015] It should be noted that the terms "a" and "a plurality of" used in this disclosure are illustrative rather than restrictive, and those skilled in the art should understand that, unless otherwise expressly indicated in the context, they should be understood as "one or more".
[0016] The names of messages or information exchanged between multiple devices in the embodiments of this disclosure are for illustrative purposes only and are not intended to limit the scope of such messages or information.
[0017] This disclosure will now be described in detail with reference to the accompanying drawings and embodiments.
[0018] In one aspect, some embodiments of this disclosure provide a siloxane terpolymer comprising a polysiloxane backbone and dimethylvinylsilyl end groups located at both ends of the polysiloxane backbone; the polysiloxane backbone is formed by random copolymerization of dimethylsiloxane structural units, methyl (3,3,3-trifluoropropyl)siloxane structural units, and methyl octylsiloxane structural units; based on the total molar amount of the dimethylsiloxane structural units, methyl (3,3,3-trifluoropropyl)siloxane structural units, and methyl octylsiloxane structural units being 100%, the content of the dimethylsiloxane structural units is 40-90 mol%, the content of the methyl (3,3,3-trifluoropropyl)siloxane structural units is 5-35 mol%, and the content of the methyl octylsiloxane structural units is 5-25 mol; the number average molecular weight M of the siloxane terpolymer is... n The molecular weight distribution index of the above-mentioned siloxane terpolymers ranges from 40,000 to 180,000 g / mol; the molecular weight distribution index of the above-mentioned siloxane terpolymers ranges from 1.7 to 2.4. For example... Figure 5 As shown, Figure 5 The diagram shows an internal test image of the prepared siloxane terpolymer, thus providing a view of the actual product.
[0019] Further reference Figure 1 ,like Figure 1 As shown, Figure 1A process 100 is shown illustrating some embodiments of a method for preparing a siloxane terpolymer according to the present disclosure. The method for preparing the siloxane terpolymer includes the following steps: Step 101: Under inert gas protection and anhydrous conditions, prepare a monomer mixture containing octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and tetramethyltetraoctylcyclotetrasiloxane.
[0020] In some embodiments, a monomer mixture comprising octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane is prepared under inert gas protection and anhydrous conditions. The mass ratio of octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane is 1:(0.12~1.84):(0.13~1.45). The inert gas is nitrogen. It should be noted that setting the above mass ratio allows for a larger molecular weight of the prepared polymer, making it more suitable for membrane preparation. The above-mentioned monomer mixture is a solution obtained by mixing octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane. It should be noted that the structure of the above-mentioned dimethylsiloxane structural unit can be represented as —Si(CH3)2—O—; the structure of the above-mentioned methyl(3,3,3-trifluoropropyl)siloxane structural unit can be represented as —Si(CH3)(CH2CH2CF3)—O—, which can also be called 3,3,3-trifluoropropylmethylsiloxane structural unit, methyltrifluoropropylsiloxane structural unit, or methyl-3,3,3-trifluoropropylsiloxane structural unit; the structure of the above-mentioned methyloctylsiloxane structural unit can be represented as —Si(CH3)(C8H 17 The dimethylsiloxane structural unit described above can be formed by the ring-opening polymerization of octamethylcyclotetrasiloxane, the methyl(3,3,3-trifluoropropyl)siloxane structural unit described above can be formed by the ring-opening polymerization of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and the methyloctylsiloxane structural unit described above can be formed by the ring-opening polymerization of tetramethyltetraoctylcyclotetrasiloxane. For example... Figure 6 As shown, Figure 6 The structural formula of tetramethyltetraoctylcyclotetrasiloxane is shown. (Example:) Figure 7 As shown, Figure 7 The structural formula of octamethylcyclotetrasiloxane is shown. (Example:) Figure 8 As shown, Figure 8 The structural formula of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane is shown.
[0021] Optionally, the aforementioned tetramethyltetraoctylcyclotetrasiloxane can be 2,4,6,8-tetramethyl-2,4,6,8-tetraoctylcyclotetrasiloxane, which can be prepared by a platinum-catalyzed hydrosilylation reaction of 2,4,6,8-tetramethylcyclotetrasiloxane with 1-octene. The molar ratio between the aforementioned 2,4,6,8-tetramethylcyclotetrasiloxane and the aforementioned 1-octene is in the range of 1:4 to 1:12, preferably 1:8 to 1:12.
[0022] Optionally, the preparation steps of the above-mentioned tetramethyltetraoctylcyclotetrasiloxane are as follows: First, the molar ratio of the above-mentioned 2,4,6,8-tetramethylcyclotetrasiloxane to the above-mentioned 1-octene was set to 1:10. Then, the reaction was carried out at 60°C to 70°C for 10 to 24 hours under the action of a platinum catalyst. Finally, after the reaction was completed, excess 1-octene and low-boiling substances were removed to obtain tetramethyltetraoctylcyclotetrasiloxane. The platinum catalyst used above can be a chloroplatinic acid isopropanol solution containing 2 wt% platinum.
[0023] In addressing the first technical problem mentioned above, and considering the application scenario of preparing protective coatings for electronic sensors, the following second technical problem often arises: ordinary similar copolymers (such as conventional dimethylsiloxane binary copolymers) cannot meet the stringent operating conditions and performance requirements of electronic sensor protective coatings due to their wide molecular weight distribution, uneven chain segment distribution, poor resistance to media and temperatures, and insufficient processability, transparency, and mechanical properties. To address the following requirements for this application scenario: adaptability to narrow molecular weight distribution, uniform chain segment distribution, high resistance to media and temperatures, and high processability, transparency, and mechanical properties, we have decided to adopt the following solution: In some alternative implementations of some embodiments, a monomer mixture comprising octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and tetramethyltetraoctylcyclotetrasiloxane can be prepared under inert gas protection and anhydrous conditions by the following steps: The first step involves adding the aforementioned 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and tetramethyltetraoctylcyclotetrasiloxane to a reaction vessel and stirring to obtain a first mixture. In practice, firstly, octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane can be weighed according to the mass ratio between them to obtain the weighed octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane. Then, the above-mentioned 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and the above-mentioned tetramethyltetraoctylcyclotetrasiloxane were added to a reaction vessel and stirred to obtain a first mixture. The first mixture can be a solution of the above-mentioned 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and the above-mentioned tetramethyltetraoctylcyclotetrasiloxane. The reaction vessel was a dry reaction vessel. It should be noted that the reason for using the above-mentioned dry reaction vessel is to obtain D3... F D4 Oct Water must not be present during the mixing process, and the mixture must not react with water.
[0024] The second step involves adding diphenylsilanediol to the first mixture described above. The amount of diphenylsilanediol added is 0.05% to 0.1% of the total mass of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and tetramethyltetraoctylcyclotetrasiloxane. In practice, the first mixture can be stirred while diphenylsilanediol is slowly added to obtain the first mixture containing diphenylsilanediol. It should be noted that the amount of diphenylsilanediol added can balance effective complexation with subsequent polymerization reactions, ensuring that the diphenylsilanediol fully complexes D3. F D4 Oct This method weakens the polarity difference between the two to form a stable pre-complexed system, laying the foundation for uniform copolymerization of ternary monomers. It also reduces the situation where excessive dosage leads to over-complexation and inhibition of subsequent ring-opening polymerization, or insufficient dosage fails to achieve effective complexation, resulting in uneven monomer mixing and abnormal product structure. Ultimately, it ensures that the product composition is uniform and the molecular weight distribution is qualified, meeting the performance requirements of pervaporation membranes.
[0025] The third step involves heating the first mixture to 30-35°C at a rate of 1-2°C / min and stirring at this constant temperature for 20-25 minutes to conduct a pre-complexation reaction, obtaining a pre-complexed system. In practice, the first mixture containing diphenylsilanediol can first be heated to 30-35°C at a uniform rate of 1-2°C / min. It should be noted that this uniform heating rate of 1-2°C / min ensures a gentler and more uniform complexation reaction, a more stable system, avoids localized overheating or uneven complexation, and maintains reaction efficiency, providing a stable pre-complexed system for subsequent uniform copolymerization. Then, while maintaining a constant temperature, the first mixture containing diphenylsilanediol is stirred and subjected to a 20-25 minute isothermal pre-complexation reaction, resulting in the first mixture after the 20-25 minute isothermal pre-complexation reaction, which is used as the pre-complexed system. The pre-complexed system is the solution obtained after the pre-complexation reaction of the first mixture containing diphenylsilanediol. It should be noted that the above-mentioned isothermal pre-complexation reaction can allow diphenylsilanediol to react with D3. F D4 Oct The complexation process is fully and uniformly carried out, which weakens the polarity difference between the two functional monomers and forms a stable and uniform pre-complexed system. This reduces the problems of uneven monomer distribution and mismatched polymerization rates during subsequent copolymerization, which is conducive to the uniform copolymerization of ternary monomers and promotes the uniformity and controllability of product structure.
[0026] The fourth step involves adding octamethylcyclotetrasiloxane to another dry reactor for activation, yielding activated octamethylcyclotetrasiloxane. In practice, the temperature is first raised to 40-45°C. Then, the octamethylcyclotetrasiloxane is stirred for 10-15 minutes to activate it, resulting in the activated octamethylcyclotetrasiloxane. It should be noted that the activation at 40-45°C breaks down the intermolecular forces within octamethylcyclotetrasiloxane, enhancing its ring-opening reactivity and allowing it to react with the pre-complexed D3. F D4 Oct The system's activity is more matched, resulting in uniform copolymerization of the subsequent ternary monomers and a regular structure, reducing problems such as uneven copolymerization and widened molecular weight distribution caused by differences in activity.
[0027] Fifth, add the pre-complexed system to the activated octamethylcyclotetrasiloxane and continue stirring for 10-15 minutes to obtain a monomer mixture. In practice, the temperature and stirring rate can be kept constant, and the pre-complexed system can be added to the activated octamethylcyclotetrasiloxane and stirred for 10-15 minutes to obtain a ternary monomer mixture as the monomer solution. It should be noted that the ternary monomer mixture ensures that the three monomers have matched activity and uniform dispersion, allowing the subsequent ring-opening polymerization reaction to proceed smoothly, synchronously, and uniformly, resulting in consistent polymer chain growth, a narrower molecular weight distribution, and a more regular product structure.
[0028] The above-mentioned optional embodiments, as an inventive point of this disclosure, solve the technical problem of "common homogeneous copolymers having wide molecular weight distribution, uneven chain segments, poor resistance to media and temperature, and insufficient processability, mechanical properties / transparency". The specific factors leading to the wide molecular weight distribution, uneven chain segments, poor resistance to media and temperature, and insufficient processability, mechanical properties / transparency of common homogeneous copolymers are as follows: The fluorosilicone monomers and long-chain alkylsilicone monomers were not pre-mixed and homogenized, nor were they pre-complexed with diphenylsilanediol. This results in poor monomer compatibility and phase separation, affecting transparency and mechanical properties. It also fails to activate the low-activity fluorosilicone monomers, leading to a significant decrease in resistance to media and high / low temperatures. Furthermore, the lack of a segmented controlled polymerization process causes the three monomers to polymerize sequentially due to differences in activity, resulting in a polymer with a disordered structure. If the above factors are addressed, the molecular weight distribution can be narrowed, the uniformity of chain segment distribution can be improved, the resistance to media and temperature can be enhanced, and the processability, transparency, and mechanical properties can be improved. To achieve this effect, the preparation method of the siloxane terpolymer disclosed herein uses raw material pretreatment and pre-complexation processes. Because the raw material pretreatment eliminates impurities, the monomers are pre-homogenized, pre-complexed, and subjected to controlled polymerization, the terpolymers are copolymerized in an orderly manner, and side reactions are suppressed. The pre-complexation activates the fluorosilicone monomers, allowing the three chain segments to synergistically exert their advantages in temperature and media resistance. The chain segment distribution is uniform, there is no obvious phase separation, and the controllability of polymerization is enhanced, reducing molding defects. It takes into account the material's fluidity, uniformity, and mechanical toughness. Therefore, it is possible to prepare coatings with narrow molecular weight distribution, uniform chain segment distribution, high resistance to media and temperature, high processability, high transparency, and high mechanical properties.
[0029] Step 102: Control the temperature of the monomer mixture to 50~65℃.
[0030] In some embodiments, the temperature of the monomer mixture can be controlled to 50-65°C. It should be noted that the reason for raising the temperature of the monomer mixture to 50-65°C is that when the temperature of the monomer mixture is below 50°C, the reaction rate is too slow, and the molecular weight of the product is too small; when the temperature of the monomer mixture is above 65°C, there are too many side reactions, the molecular weight distribution is relatively wide, resulting in poor uniformity of the obtained polymer and easy cross-linking.
[0031] Step 103: Add a catalyst to carry out a ring-opening polymerization reaction to obtain a polymerization reaction solution.
[0032] In some embodiments, a catalyst is added to carry out a ring-opening polymerization reaction to obtain a polymerization reaction solution. The polymerization reaction solution is the solution obtained after the ring-opening polymerization reaction of the monomer mixture described above. The catalyst is anhydrous trifluoromethanesulfonic acid or a complex acid containing anhydrous trifluoromethanesulfonic acid, and the amount of catalyst added is 0.02% to 0.1% of the total mass of octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane. The anhydrous trifluoromethanesulfonic acid can be anhydrous trifluoromethanesulfonic acid. The reaction time of the ring-opening polymerization reaction is in the range of 0.5 to 1 hour. The reason for setting the range to 0.02% to 0.1% is that when the catalyst content is below 0.02%, the reaction time will be too long and the reaction will be incomplete. When the catalyst content is above 0.1%, more uncertain side reactions will occur, resulting in an increase in the variety of products obtained. The reaction time for the above ring-opening polymerization reaction ranges from 10 to 60 minutes, depending on the viscosity of the mixture containing the catalyst during the polymerization process. It should be noted that ring-opening polymerization can open and copolymerize three cyclic siloxane monomers to form a linear terpolymer with a uniform structure and controllable molecular weight. Using trifluoromethanesulfonic acid as a catalyst can efficiently catalyze the ring-opening of cyclic siloxane monomers, increasing the polymerization rate and monomer conversion, thus ensuring a stable ring-opening polymerization reaction. Figure 9 As shown, Figure 9 The structural formula of trifluoromethanesulfonic acid is shown.
[0033] In addressing the second technical problem mentioned above, and considering the application scenario of preparing composite membranes for organic solvent recovery and purification, the following third technical problem often arises: the composite membrane needs to withstand long-term exposure to high-concentration organic solvents and harsh conditions at temperatures of 80-150°C, while maintaining continuous and stable operation. Traditional membranes suffer from poor solvent resistance, uneven pore size, poor mechanical stability, and are easily damaged, making them unsuitable. To meet the following requirements for this application scenario—adaptability to long-term exposure to high-concentration organic solvents, adaptability to harsh conditions at 80-150°C, and the need for continuous and stable operation—we have decided to adopt the following solution: In some alternative implementations of certain embodiments, the catalyst and ring-opening polymerization reaction can be prepared by the following steps: The first step involves placing trifluoromethanesulfonic acid and perfluoro-1-butanesulfonic acid in an anhydrous, sealed container at a mass ratio of (3-5):1 and stirring for 3-5 minutes to obtain a composite acid catalyst. This composite acid catalyst characterizes the mixed trifluoromethanesulfonic acid and perfluoro-1-butanesulfonic acid. It should be noted that the trifluoromethanesulfonic acid and perfluoro-1-butanesulfonic acid synergistically adapt to the ring-opening requirements of the three monomers. Trifluoromethanesulfonic acid ensures polymerization efficiency, while perfluoro-1-butanesulfonic acid balances the activity of each monomer, reducing copolymerization inhomogeneity and ensuring a uniform product structure. Mixing trifluoromethanesulfonic acid and perfluoro-1-butanesulfonic acid at a mass ratio of 3-5:1 fully leverages their synergistic catalytic effect, improving polymerization efficiency, balancing monomer activity, and reducing polymerization runaway and copolymerization inhomogeneity.
[0034] The second step involves placing trimethylchlorosilane in a sealed container as a proton reactivity modifier. The mass of this proton reactivity modifier is 0.02% to 0.05% of the total mass of the aforementioned octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane. It should be noted that using trimethylchlorosilane as a proton reactivity modifier can regulate the proton reactivity of the system, suppress ring-opening polymerization side reactions, control the polymerization rate and product molecular weight distribution, and ensure uniform product structure. The mass of the proton reactivity modifier, at 0.02% to 0.05% of the total mass, allows for the regulation of the system's proton reactivity: too low a concentration will not effectively suppress side reactions or regulate molecular weight distribution; too high a concentration will inhibit the ring-opening polymerization reaction, leading to reaction inhibition and a decrease in monomer conversion. This proportion enhances its regulatory effect without affecting the polymerization process.
[0035] The third step involves adding 60%–70% of the total amount of the catalyst to the monomer mixture at a stirring rate of 0.5–1 mL / min while stirring at 200–300 rpm, resulting in a monomer mixture with the catalyst added. In practice, the monomer mixture can be stirred while simultaneously adding 60%–70% of the total amount of the catalyst. The stirring rate is 200–300 rpm, and the adding rate is 0.5–1 mL / min. It should be noted that adding 60%–70% of the total amount of the catalyst helps reduce the risk of excessively high initial catalyst concentration leading to rapid polymerization and uneven copolymerization. This also provides sufficient catalytic activity for the initial ring-opening polymerization, ensuring a smooth start-up of the reaction and laying the foundation for subsequent catalyst replenishment and accurate reaction control. The stirring rate of the above stirring is 200~300 r / min, and the dropping rate is 0.5~1 mL / min. This can ensure that the added composite acid catalyst is uniformly dispersed in the system, reduce the risk of uncontrolled polymerization and uneven copolymerization caused by excessively high local catalytic concentration, and at the same time ensure a smooth start-up of the initial ring-opening polymerization, taking into account both reaction efficiency and system uniformity.
[0036] Fourth, after the addition is complete, maintain the temperature, stirring rate, inert gas protection, and anhydrous conditions, and continue stirring the monomer mixture containing the catalyst to carry out the initial ring-opening polymerization reaction. It should be noted that the initial ring-opening polymerization reaction can gently initiate monomer ring-opening, achieve preliminary uniform bonding, and steadily advance the reaction, laying the foundation for accurate subsequent control and improving the uniformity of the product.
[0037] Fifth, after the initial ring-opening polymerization reaction begins, the viscosity of the above mixture is measured every five minutes using a rotational viscometer to obtain the first viscosity. This first viscosity characterizes the viscosity of the monomer mixture containing the catalyst at the current moment.
[0038] Step 6: In response to the aforementioned viscosity reaching the replenishment condition, a replenishment operation is performed. In practice, the remaining catalyst is added to the monomer mixture containing the catalyst, and the proton activity regulator is added simultaneously. The replenishment conditions are a viscosity of 500-800 mPa·s and a catalyst addition rate of 0.5-1 mL / min. It should be noted that the replenishment operation replenishes catalytic activity and simultaneously adds the proton activity regulator, precisely controlling the polymerization rate and molecular weight distribution, reducing insufficient activity in the later stages of polymerization, and ensuring uniform copolymerization and product compliance. The reason for setting the viscosity at 500-800 mPa·s is that at this stage, the initial polymerization reaction proceeds smoothly, and the monomers begin to open and connect. This reduces the risk of uncontrolled polymerization due to replenishment at excessively low viscosity, and also reduces the risk of uneven catalysis and a broadened molecular weight distribution due to replenishment at excessively high viscosity, thus improving the replenishment effect and ensuring controllable subsequent polymerization and product uniformity.
[0039] Step 7: After the addition is complete, adjust the stirring speed to 300-350 r / min to carry out the later ring-opening polymerization reaction, and periodically monitor the second viscosity of the system. In practice, after the addition is complete, keep the temperature and inert gas protection constant, adjust the stirring speed to 300-350 r / min to carry out the later ring-opening polymerization reaction, and simultaneously measure the viscosity of the monomer mixture containing the above catalyst every five minutes using a rotational viscometer to obtain the second viscosity. The second viscosity characterizes the viscosity at the current moment of measurement. It should be noted that adjusting the stirring speed to 300-350 r / min in the later ring-opening polymerization enhances mass transfer, ensures uniform dispersion of the added catalyst and proton activity regulator, balances the later polymerization activity, reduces excessively rapid or uneven local polymerization, and improves the uniformity of the product structure and controllable molecular weight.
[0040] Step 8: In response to the second viscosity reaching 1800~2600 mPa·s, the ring-opening polymerization reaction is terminated, yielding the polymerization reaction liquid. It should be noted that when the viscosity reaches 1800~2600 mPa·s, it can improve the complete copolymerization of monomers, ensure the product meets the standards, reduce incomplete polymerization or system agglomeration, and improve the smoothness of the process.
[0041] The above optional embodiments, as an inventive point of this disclosure, solve the technical problem of "poor solvent resistance and uneven pore size of traditional membranes". The specific factors leading to poor solvent resistance and uneven pore size of traditional membranes are as follows: Traditional membranes use a single catalyst for polymerization, resulting in low purity of raw materials, many by-products, and a lack of solvent-resistant groups in the molecular structure, making them easily corroded and swollen by organic solvents. Furthermore, they do not employ staged, precise temperature and rate-controlled ring-opening polymerization, making the polymerization process uncontrollable, leading to uneven molecular chain growth, and consequently, disordered pore size, poor mechanical stability, and susceptibility to damage. If the above factors are addressed, the membrane can withstand long-term exposure to high concentrations of organic solvents and harsh operating conditions at 80-150°C, improving solvent resistance and mechanical stability. To achieve this, the method for preparing the siloxane terpolymer disclosed herein uses a crosslinking agent prepared by combining refined cyclic and linear crosslinking agents to prepare the terpolymer composite membrane. Therefore, the catalyst and the staged ring-opening polymerization process are effective. The catalyst improves the polymerization efficiency and purity of the terpolymer, reducing the impact of impurities on the membrane's separation performance and solvent resistance. The staged ring-opening polymerization precisely controls the polymerization process, achieving precise pore size distribution, enhancing molecular stability, improving the membrane's mechanical strength and temperature and solvent resistance, and improving the membrane's stable operation under harsh conditions. This, in turn, enhances the solvent resistance and mechanical stability of the prepared composite membrane.
[0042] Step 104: Tetramethyldivinyldisiloxane is added to the polymerization reaction solution to carry out the end-group sealing reaction, and the end-group sealed reaction solution is obtained.
[0043] In some embodiments, tetramethyldivinyldisiloxane is added to the above polymerization reaction solution to perform an end-group sealing reaction, resulting in a sealed reaction solution. The amount of tetramethyldivinyldisiloxane added is 0.1% to 0.6% of the total mass of octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane, and the duration of the end-group sealing reaction is 1 to 3 hours. It should be noted that the end-group sealing reaction can block the active end groups of the polymerization product, terminate further polymerization, regulate the molecular weight and molecular weight distribution of the product, and improve the product's stability, temperature resistance, and mechanical properties, thus meeting the requirements for the preparation and use of pervaporation membranes. Tetramethyldivinyldisiloxane, as a sealing agent, can precisely block active end groups, regulate molecular weight, improve product performance, and has good compatibility and thorough sealing, making it suitable for systems and industrial production, reducing performance deviations. It should be noted that when the amount of tetramethyldivinyldisiloxane added is set below 0.1%, it easily leads to the regeneration of more types of cyclosiloxanes by a large number of siloxane chains that are slower to contact the end-capping agent during the polymerization reaction, thus reducing the amount of siloxane terpolymer formed. Conversely, when the amount of tetramethyldivinyldisiloxane added is set above 0.6%, most short-chain, fast-contacting end-capping agents are capped, forming a large number of small-molecule polymers, which is detrimental to film formation. Therefore, setting the amount of tetramethyldivinyldisiloxane added between 0.1% and 0.6% is more appropriate. Figure 10 As shown, Figure 10 It shows Figure 10 The structural formula of the capping agent.
[0044] Step 105: Cool the end-capped reaction solution to obtain a cooled reaction solution.
[0045] In some embodiments, the end-capped reaction solution is cooled to obtain a cooled reaction solution. In practice, the end-capped reaction solution can be cooled to room temperature to obtain a cooled reaction solution.
[0046] Step 106: Add a quenching reagent to the cooled reaction solution to perform quenching treatment, and obtain a quenched reaction solution.
[0047] In some embodiments, a quenching agent can be added to the cooled reaction solution, stirred to perform quenching treatment, and then preliminarily washed with water to obtain a quenched reaction solution. The quenching agent is a sodium bicarbonate solution or a dilute alkaline solution. It should be noted that the quenching treatment involves neutralizing the remaining catalyst in the system with the quenching agent, thereby completely deactivating the catalyst and terminating the polymerization reaction. The concentration of the dilute alkaline solution can be 15%.
[0048] Step 107: Wash the quenched reaction solution with water until the aqueous phase is neutral, and separate to obtain the organic phase.
[0049] In some embodiments, the reaction solution after the above quenching treatment can be washed with water until the aqueous phase is neutral, and the organic phase can be separated. It should be noted that the washing treatment can remove residual catalysts and water-soluble byproducts from the system, reduce the impact of residual acidic or alkaline substances on the efficiency of subsequent end-group capping reactions, and reduce the possibility of product degradation, cross-linking, or performance deviation.
[0050] Step 108: The organic phase is subjected to depressurization to remove volatiles, resulting in a siloxane terpolymer.
[0051] In some embodiments, the above-mentioned organic phase can be subjected to vacuum degassing to remove volatiles, yielding a siloxane terpolymer. The siloxane terpolymer is an α,ω-divinyl-terminated poly(dimethylsiloxane-co-methyl(3,3,3-trifluoropropyl)siloxane-co-methyloctylsiloxane), a linear polymer with a number-average molecular weight M. n The concentration ranges from 40,000 to 180,000 g / mol, and the molecular weight distribution index ranges from 1.7 to 2.4. For example... Figure 11 As shown, Figure 11 Based on the chemical formula of the siloxane terpolymer and its preparation method disclosed herein, Figure 11 In this context, x, y, and z represent the average degree of aggregation of the corresponding structural units, and all three are greater than 0. For example... Figure 12 As shown, Figure 12 A schematic diagram of the synthesis process of siloxane terpolymers is shown. In practice, the above organic phase can be subjected to depressurization treatment to remove volatiles under conditions of 60~90℃ and a vacuum degree of -0.08~-0.095 MPa to obtain siloxane terpolymers.
[0052] In addressing the third technical problem mentioned above, and considering the application scenario of preparing protective coatings for precision aerospace components, the following fourth technical problem often arises: ordinary copolymers of the same type are prone to coating peeling and cracking due to residual impurities and structural damage, thus failing to provide protection. To meet the following requirements for this application scenario—namely, the need for no residual impurities and high structural stability—we have decided to adopt the following solution: In some optional implementations of certain embodiments, the above-mentioned organic phase can be subjected to depressurized removal of volatiles through the following steps to obtain a siloxane terpolymer: The first step involves transferring the organic phase to a rotary evaporator while continuously introducing a small amount of nitrogen gas into the evaporator, resulting in a rotary evaporator containing the organic phase product. The amount of organic phase transferred is 1 / 3 to 2 / 3 of the volume of the rotary evaporator, which must be dry and clean.
[0053] The second step is to fix the rotary evaporation flask containing the organic phase product onto a vacuum rotary evaporator.
[0054] The third step involves heating and depressurizing the rotary flask containing the organic phase product. In practice, the flask is heated to 60-70°C using a constant-temperature water bath while simultaneously turning on the vacuum pump and slowly adjusting the vacuum level to -0.08 to -0.09 MPa. The heating rate is 2-3°C / min. It should be noted that heating the flask to 60-70°C efficiently removes low-boiling-point impurities, balancing impurity removal efficiency with product stability, and minimizing the impact of excessively high or low temperatures on product quality. Setting the vacuum level to -0.08 to -0.09 MPa lowers the system's boiling point, facilitating impurity volatilization, balancing efficient impurity removal with product retention, and reducing losses or incomplete impurity removal due to unsuitable vacuum levels. The heating rate of 2-3°C / min ensures a uniform temperature rise, reducing product degradation and agglomeration, and improving the stability of impurity removal and the uniformity of product structure.
[0055] The fourth step involves stirring the organic phase in a rotary evaporator for 2-3 hours to remove impurities, resulting in a preliminarily purified organic phase product.
[0056] The fifth step involves heating the pre-purified organic phase product to 80-90°C using a constant-temperature water bath, and gradually increasing the vacuum level to -0.09 to -0.095 MPa by adjusting the vacuum pump. The heating rate is 2-3°C / min. It should be noted that heating to 80-90°C and achieving a vacuum level of -0.09 to -0.095 MPa at higher temperatures and vacuum levels allows for deeper purification, effectively removing residual non-volatile impurities, trace monomers, and solvents from the system. This ensures more thorough impurity removal, reduces thermal degradation or structural damage to the product, and improves product purity and stability.
[0057] Step 6: Maintaining a constant stirring rate, introduce nitrogen gas into the organic phase product after deep purification until the pressure returns to atmospheric pressure. Simultaneously, close the constant temperature water bath and allow it to cool naturally to 60°C. The nitrogen gas introduction rate is 10-15 mL / min. It should be noted that introducing nitrogen gas to restore atmospheric pressure breaks the vacuum, protects the product from oxidation, and reduces backflow contamination from external air. Closing the water bath and allowing natural cooling to 60°C reduces product agglomeration and degradation due to rapid cooling, ensuring product structural stability. Controlling the nitrogen flow rate at 10-15 mL / min ensures a smooth vacuum breaking process, reducing the risk of product splashing or excessive system disturbance due to excessive flow rate, while also providing inert protection.
[0058] Step 7: Maintaining 60°C, atmospheric pressure, and the aforementioned nitrogen flow rate, purge the deeply purified organic phase product with nitrogen for 30 minutes to obtain the siloxane terpolymer. It should be noted that the purging process further removes residual trace light component impurities and moisture, while simultaneously replacing air in the system, reducing product oxidation, and improving product purity and stability.
[0059] The above optional embodiments, as an inventive point of this disclosure, solve the technical problem of "common homogeneous copolymers being prone to structural damage due to impurity residues". Specific factors leading to the structural damage of common homogeneous copolymers due to impurity residues are as follows: The single impurity removal method, with a fixed temperature and vacuum level, cannot simultaneously address both low-boiling-point and medium-to-high-boiling-point impurities, making complete removal difficult; the lack of nitrogen purging at the end easily leads to secondary residues of trace impurities and the introduction of moisture from the air; the lack of precise parameter control and structural protection measures during rotary evaporation, specifically manifested as uncontrolled heating rate leading to localized overheating, lack of stirring or insufficient stirring causing uneven heating, lack of nitrogen protection throughout the process leading to oxidative hydrolysis, and the lack of clear parameter standards. If the above factors are resolved, the effect of no impurity residue and high structural stability can be achieved. To achieve this effect, the preparation method of the siloxane terpolymer disclosed herein uses a staged temperature and pressure controlled nitrogen-protected vacuum rotary evaporation process. Because the staged temperature and pressure controlled nitrogen-protected vacuum rotary evaporation process adopts a step-by-step temperature and pressure control mode, it can completely remove both low-boiling-point and non-volatile impurities. Through full nitrogen protection, the secondary residue of impurities and the introduction of moisture are reduced. The heating rate, stirring requirements and parameter standards are clearly defined to reduce local overheating, uneven heating, oxidation hydrolysis and lack of parameter standards, thereby improving the purity and structural stability of the product. Therefore, a coating with no impurity residue and high structural stability can be prepared.
[0060]
experiment
[0061] (2) Polymerization: After the system temperature stabilizes at 60℃, 0.043g of anhydrous trifluoromethanesulfonic acid is quickly injected with a syringe, which is 0.1% of the total mass of the monomer. The temperature is kept constant at 60℃ and the reaction is stirred for 30 minutes. The viscosity of the system increases significantly.
[0062] (3) End-capping: Tetramethyldivinyldisiloxane (MM) is added to the above reaction solution. Vi 0.257g, which is 0.6% of the total mass of the monomer, was added and stirred at 60℃ for 3 hours.
[0063] (4) Post-treatment: Cool the reaction solution to room temperature, transfer it to a separatory funnel, quench the catalyst with saturated sodium bicarbonate aqueous solution, wash repeatedly with an appropriate amount of distilled water 5 to 6 times until the aqueous phase is neutral (pH 6 to 8), separate the upper oily product, add anhydrous magnesium sulfate and dry overnight, filter, and then evaporate the filtrate at 80℃ and -0.095MPa for 1 hour to remove residual water and low-boiling substances, and obtain transparent, viscous vinyl-terminated silicone oil product A with a yield of 95.2%.
[0064] Example 2: Synthesis of terpolymers with different monomer ratios The steps in this embodiment are basically the same as those in Embodiment 1, except that the mass ratio of the monomers is changed. The specific steps are as follows: (1) Feeding: 10 g D4, 1.2 g D3 F 1.3gD4 Oct The mass ratio is D4:D3 F :D4 Oct =1:0.12:0.13; (2) Polymerization and End-Capping: The catalyst was anhydrous trifluoromethanesulfonic acid, used at 0.1% of the total monomer mass; the reaction temperature was 60℃; and the polymerization time was 30 minutes. End-capping agent MM Vi The dosage is 0.6% of the total monomer mass, and the end-capping reaction time is 3 hours.
[0065] (3) Post-processing: Same as in Example 1, viscous silicone oil product B was obtained with a yield of 96.8%.
[0066] Example 3: Synthesis of terpolymers with different catalyst dosages This embodiment aims to investigate the effect of catalyst dosage on the reaction, and the steps are basically the same as in Example 1: (1) Feeding: The types, proportions and amounts are exactly the same as in Example 1.
[0067] (2) Polymerization and End-Capping: The catalyst was anhydrous trifluoromethanesulfonic acid, with its dosage reduced to 0.02% of the total monomer mass. The reaction temperature was 65℃, and the polymerization time was extended to 40 minutes. End-capping agent MM Vi The dosage is 0.6% of the total monomer mass, and the end-capping reaction time is 3 hours.
[0068] (3) The same post-processing as in Example 1 was performed to obtain viscous silicone oil product C with a yield of 92.8%.
[0069] Example 4: Synthesis of terpolymers with different capping agent amounts.
[0070] This embodiment aims to control the molecular weight by adjusting the amount of capping agent, and the steps are basically the same as in Example 1: (1) The monomer type, ratio, amount and catalyst amount are exactly the same as in Example 1.
[0071] (2) Add the capping agent MM Vi The amount of [agent] used is reduced to 0.1% of the total mass of the monomer, while other conditions remain unchanged.
[0072] (3) Post-processing: Same as in Example 1, to obtain a viscous silicone oil product D with a higher molecular weight, with a yield of 94.5%.
[0073] Example 5: Synthesis of vinyl-terminated terpolymers (1) Feeding: Under nitrogen protection, add 10g of octamethylcyclotetrasiloxane, 8.0g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and 11g of tetramethyltetraoctylcyclotetrasiloxane sequentially to a dry four-necked flask. The total monomer feed mass ratio is controlled to be D4:D3. F :D4 Oct = 1:0.8:1.1. Start stirring and heat the oil bath to 56℃.
[0074] (2) Polymerization: After the system temperature stabilizes at 56℃, 0.017g of anhydrous trifluoromethanesulfonic acid is injected quickly with a syringe. The trifluoromethanesulfonic acid is 0.06% of the total mass of the monomer. The temperature is kept constant at 56℃ and the reaction is stirred for 40 minutes. The viscosity of the system increases significantly.
[0075] (3) End-capping: Tetramethyldivinyldisiloxane (MM) is added to the above reaction solution. Vi 0.174 g, which is 0.6% of the total mass of the monomer, was added and stirred at 56°C for 3 hours.
[0076] (4) Post-treatment: Cool the reaction solution to room temperature, transfer it to a separatory funnel, quench the catalyst with saturated sodium bicarbonate aqueous solution, wash repeatedly with an appropriate amount of distilled water 5-6 times until the aqueous phase is neutral and the pH is in the range of 6-8, separate the upper oily product, add anhydrous magnesium sulfate and dry overnight, filter, and then evaporate the filtrate at 80℃ and -0.095MPa for 1 hour to remove residual water and low boiling matter, and obtain transparent, viscous vinyl-terminated silicone oil product E with a yield of 96.2%.
[0077] Example 6: Synthesis of vinyl-terminated terpolymers (1) Feeding: Under nitrogen protection, add 10g of octamethylcyclotetrasiloxane, 17g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and 9.0g of tetramethyltetraoctylcyclotetrasiloxane sequentially to a dry four-necked flask. The total monomer feed mass ratio is controlled to be D4:D3. F :D4 Oct = 1:1.7:0.9. Start stirring and heat the oil bath to 58℃.
[0078] (2) Polymerization: After the system temperature stabilizes at 58℃, 0.018g of anhydrous trifluoromethanesulfonic acid is quickly injected with a syringe, which is 0.05% of the total mass of the monomer. The temperature is kept constant at 58℃ and the reaction is stirred for 30 minutes. The viscosity of the system increases significantly.
[0079] (3) End-capping: Tetramethyldivinyldisiloxane (MM) is added to the above reaction solution. Vi 0.108g, which is 0.3% of the total mass of the monomer, was added and stirred at 58℃ for 3 hours.
[0080] (4) Post-treatment: Cool the reaction solution to room temperature, transfer it to a separatory funnel, quench the catalyst with saturated sodium bicarbonate aqueous solution, wash repeatedly with an appropriate amount of distilled water 5-6 times until the aqueous phase is neutral and the pH is in the range of 6-8, separate the upper oily product, add anhydrous magnesium sulfate and dry overnight, filter, and then evaporate the filtrate at 80℃ and -0.095MPa for 1 hour to remove residual water and low boiling matter, and obtain transparent, viscous vinyl-terminated silicone oil product F with a yield of 95.2%.
[0081] Example 7: Synthesis of vinyl-terminated terpolymers (1) Feeding: Under nitrogen protection, add 10g of octamethylcyclotetrasiloxane, 14g of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and 11g of tetramethyltetraoctylcyclotetrasiloxane sequentially to a dry four-necked flask. The total monomer feed mass ratio is controlled to be D4:D3. F :D4 Oct=1:1.4:1.1. Start stirring and heat the oil bath to 60℃.
[0082] (2) Polymerization: After the system temperature stabilizes at 60℃, 0.018g of anhydrous trifluoromethanesulfonic acid is quickly injected with a syringe, which is 0.05% of the total mass of the monomer. The temperature is kept constant at 60℃ and the reaction is stirred for 30 minutes. The viscosity of the system increases significantly.
[0083] (3) End-capping: Tetramethyldivinyldisiloxane (MM) is added to the above reaction solution. Vi 0.210g, which is 0.6% of the total mass of the monomer, was added and stirred at 60℃ for 3 hours.
[0084] (4) Post-treatment: Cool the reaction solution to room temperature, transfer it to a separatory funnel, quench the catalyst with saturated sodium bicarbonate aqueous solution, wash repeatedly with an appropriate amount of distilled water 5-6 times until the aqueous phase is neutral and the pH is in the range of 6-8, separate the upper oily product, add anhydrous magnesium sulfate and dry overnight, filter, and then evaporate the filtrate at 80℃ and -0.095MPa for 1 hour to remove residual water and low boiling matter, and obtain transparent, viscous vinyl-terminated silicone oil product G with a yield of 93.0%.
[0085] Comparative Example 1: Synthesis of a fluorine-free binary copolymer (PDMS-co-POMS) This comparative example is used to illustrate the role of introducing the fluorine unit.
[0086] (1) Feeding: Under nitrogen protection, add 18.35g D4 and 17.25g D4. Oct The mass ratio is D4:D4 Oct =1:0.94. Not joining D3 F Turn on the stirrer and heat to 60°C.
[0087] (2) Polymerization and End-Capping: Polymerization and End-Capping: Add 0.028 g of trifluoromethanesulfonic acid (0.08% of the total monomer mass) and react for 30 minutes. Add MM Vi 0.071 g, which is 0.2% of the total mass of the monomer, was added, and the reaction continued for 2 hours.
[0088] (3) Post-processing: Same as in Example 1, to obtain a vinyl-terminated silicone oil product, denoted as H (fluorine-free). Figure 4 As shown, Figure 4 A comparison graph showing the water contact angle test results of Comparative Example 1 (fluorine-free) and the product of Example 1 is presented.
[0089] Comparative Example 2: Synthesis of Octyl-Free Dipolymer (PDMS-co-PMTFPS) This comparative example is used to illustrate the role of introducing long-chain alkyl units.
[0090] (1) Feeding: Under nitrogen protection, add 16.28g D4 and 23.1g D3. F The mass ratio is D4:D3 F = 1:1.42. D4 not included. Oct Turn on the stirrer and heat to 60°C.
[0091] (2) Polymerization and end-capping: Add 0.394 g of trifluoromethanesulfonic acid (1.0% of the total monomer mass) and react for 30 minutes. Add MM. Vi 0.079g, which is 0.2% of the total mass of the monomer, was added, and the reaction continued for 5 hours.
[0092] (3) Post-processing: Same as in Example 1, to obtain vinyl-terminated silicone oil product, denoted as I (octyl-free).
[0093] Results and Analysis: The products obtained in the above embodiments and comparative examples were characterized structurally and tested for performance. The results are as follows: 1. Structural characterization: through FT-IR (e.g., Figure 2 As shown, Figure 2 The Fourier transform infrared (FT-IR) spectrum and ¹H-NMR (e.g., ) of the ternary copolymer synthesized in Example 1 are shown. Figure 3 As shown, Figure 3 The proton NMR spectrum of the ternary copolymer synthesized in Example 1 is shown. 1 The 1H-NMR spectrum confirmed the successful synthesis of A. The FT-IR spectrum showed Si-O-Si (~1020 cm⁻¹). - ¹), Si-CH3 (~1260cm) - ¹), CF (~1200cm) - ¹) and Si-CH2(CH2)6CH3 (~2960, 2930, 2860 cm⁻¹) - ¹) Characteristic absorption peaks. ¹H-NMR spectra show chemical shifts δ 0.0-0.2 ppm (Si-CH₂). * 3), 0.4-0.6ppm (Si-CH) * 2 - CH2 - CF3), 2-2.3ppm (Si-CH2) - CH * 2 - The characteristic peaks at 0.8-0.9 ppm (Si-CH2-(CH2)6-CH3) and 5.7-6.1 ppm (Si-CH=CH2) confirmed the structure of the target terpolymer, and the proportion of each unit was basically consistent with the feed ratio.
[0094] 2. The performance test results of the example are shown in the table below: Table 1
[0095] Table 1 lists the molecular weights and swelling ratios in toluene of the polymers obtained in the examples and comparative examples. Regarding solvent resistance, Example A exhibited a swelling ratio of 58%, higher than Comparative Example I (which only introduced a non-octyl segment, with a swelling ratio of 45%), but significantly lower than Comparative Example H (which did not contain a fluorinated structural unit, with a swelling ratio of 185%). This result indicates that the methyl 3,3,3-trifluoropropylsiloxane structural unit still plays a major role in reducing excessive swelling of the polymer in organic solvents; the introduction of the fluorinated segment significantly enhances the solvent resistance advantage. Meanwhile, compared to Polymer I (which does not contain an octyl segment), the presence of the long-chain alkyl structure in Example A improves the compatibility between the polymer and the organic phase, resulting in better processing adaptability during subsequent coating and film formation.
[0096] Examples A differ from Examples B, C, D, E, F, and G in monomer feed ratio, catalyst dosage, and capping agent. The resulting products exhibit corresponding changes in properties such as number-average molecular weight and swelling ratio, indicating that the molecular weight of the polymer can be controlled by adjusting the feed composition, catalyst dosage, capping agent dosage, reaction temperature, and reaction time. This result further demonstrates that the ternary random copolymer system described in this application is not a single, fixed-composition polysiloxane material, but rather a functional siloxane copolymer system whose composition can be designed around solvent resistance, organophilicity, film-forming processability, and molecular weight requirements.
[0097] Therefore, by simultaneously introducing fluorinated side groups and long-chain alkyl side groups into the polysiloxane backbone and combining it with vinyl end-capping design, the resulting siloxane terpolymer can achieve a good balance between solvent resistance, organic affinity, molecular weight tunability and subsequent crosslinking film formation adaptability, making it suitable as a base polymer for the selective separation layer of pervaporation composite membranes.
[0098] The above-described embodiments of this disclosure have the following beneficial effects: the preparation methods of siloxane terpolymers according to some embodiments of this disclosure can achieve a good balance between low surface energy, solvent swelling resistance, hydrophobicity and organic affinity, and processability for film formation. This makes them suitable as the base polymer for the selective separation layer of pervaporation composite membranes, which is beneficial for improving the application adaptability of siloxane materials in organic solvent separation, azeotropic system separation, and high-stability membrane materials. Specifically, the reason why it is difficult to achieve a good balance between low surface energy, solvent swelling resistance, hydrophobicity and organic affinity, and processability for film formation, resulting in poor application adaptability of siloxane materials in organic solvent separation, azeotropic system separation, and high-stability membrane materials, is that although polydimethylsiloxane has good segmental flexibility and organic affinity, it is prone to significant swelling in non-polar or weakly polar organic solvents, leading to insufficient dimensional stability, selectivity retention, and long-term operational stability of the prepared membrane layer. Fluorinated siloxane structural units can reduce the surface energy of materials and improve solvent resistance, but when fluorinated side groups are simply introduced, the compatibility between the polymer and some organic phases and the adaptability of film formation processing are still limited. Long-chain alkyl side groups are beneficial to enhance hydrophobic and organic-friendly properties and organic phase compatibility, but without the synergistic regulation of fluorinated structural units, it is difficult to effectively suppress excessive swelling caused by organic solvents, resulting in poor film preparation performance. Existing binary siloxane copolymers usually focus on improving a single property, making it difficult to simultaneously achieve low surface energy, solvent swelling resistance, organic-friendly compatibility, and subsequent crosslinking film formation ability, resulting in poor performance in use. Based on this, some embodiments of the present disclosure of the method for preparing siloxane terpolymers include: first, preparing a monomer mixture containing octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane under inert gas protection and anhydrous conditions. Thus, the prepared monomer mixture can be obtained. Then, the temperature of the monomer mixture is controlled to 50-65°C. This allows for the treatment of the monomer mixture. Next, a catalyst is added, and a ring-opening polymerization reaction is carried out to obtain a polymerization reaction solution. This yields a reaction solution after polymerization. Then, tetramethyldivinyldisiloxane is added to the polymerization reaction solution to perform an end-group sealing reaction, yielding a sealed reaction solution. This can be used to prepare an organic phase. Next, the sealed reaction solution is cooled to obtain a cooled reaction solution. This yields a cooled reaction solution. Then, a quenching agent is added to the cooled reaction solution to perform a quenching treatment, yielding a quenched reaction solution. This quenched reaction solution is then used to separate the organic phase. Next, the quenched reaction solution is washed with water until the aqueous phase is neutral, and the organic phase is separated. This yields the separated organic phase.Finally, the above organic phase is subjected to reduced pressure to remove volatiles, yielding a siloxane terpolymer, wherein the siloxane terpolymer is an α,ω-divinyl-terminated poly(dimethylsiloxane-co-methyl(3,3,3-trifluoropropyl)siloxane-co-methyloctylsiloxane). Thus, the prepared siloxane terpolymer can be obtained. Because the above method for preparing the siloxane terpolymer takes into account the differences in reactivity and structural characteristics of the two monomers, methyltrifluoropropyl and methyloctyl, rather than using conventional copolymerization conditions, it achieves efficient and controllable copolymerization of the two functional monomers on the same PDMS backbone. Since this method for preparing the siloxane terpolymer is specifically developed for the reaction characteristics of the three monomers, rather than using the preparation process of binary copolymers, it solves the problem of the lack of simple, mild, efficient, and controllable preparation methods in existing technologies. Because of the introduction of methyl (3,3,3-trifluoropropyl)siloxane structural units, its surface energy can be reduced to below 15 mN / m, instead of the approximately 22 mN / m of traditional PDMS. This compensates for the weak intermolecular forces and lack of low surface energy functional groups in traditional PDMS, thereby improving its resistance to swelling in non-polar solvents and making it suitable for harsh oily environments and extremely oleophobic applications. Furthermore, because methyl octylsiloxane structural units are introduced simultaneously, rather than retaining only the single PDMS molecular structure, the compatibility of the polymer with various organic solvents is effectively improved, breaking its application limitations in solvent separation and other fields. Moreover, because this terpolymer does not only introduce one functional modifying group but also integrates the advantages of fluorine groups and long-chain alkyl groups, it achieves a synergistic improvement in ultra-low surface energy, excellent solvent resistance, and good organic compatibility, overcoming the shortcomings of existing binary copolymers. Compared to polydimethylsiloxane, the prepared siloxane terpolymers, while maintaining good film-forming properties and chain segment flexibility, can reduce the excessive swelling tendency of the polymer in organic solvents and improve the dimensional stability and performance retention of the material in high-concentration organic solvents or long-term solvent separation environments. Compared with pure fluorinated siloxane polymers, the introduction of methyl octylsiloxane structural units is beneficial to improving the compatibility between the polymer and the organic phase, and enhancing the processing adaptability in subsequent coating and crosslinking film formation processes. Through ring-opening copolymerization of octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and tetramethyltetraoctylcyclotetrasiloxane, and by using vinyl end-capping agents to regulate molecular weight and end-group structure, siloxane terpolymers with specific compositional ranges, molecular weight ranges, and molecular weight distributions can be prepared under relatively mild conditions. This method facilitates the synergistic introduction of fluorinated side groups and long-chain alkyl side groups into the same polysiloxane backbone, overcoming the shortcomings of existing binary siloxane copolymers that cannot simultaneously achieve solvent resistance, organophilicity, compositional tunability, and adaptability to subsequent crosslinking and film formation.Therefore, a good balance can be achieved between low surface energy, solvent swelling resistance, hydrophobicity and organic affinity, and processability into film. It is suitable as a base polymer for the selective separation layer of pervaporation composite membranes, which is beneficial to improving the application adaptability of siloxane materials in the fields of organic solvent separation, azeotropic system separation and high-stability membrane materials.
[0099] The above description is merely a selection of preferred embodiments of this disclosure and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in the embodiments of this disclosure is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the above-described inventive concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features with similar functions disclosed in the embodiments of this disclosure.
Claims
1. A siloxane terpolymer, characterized in that, The siloxane terpolymer comprises a polysiloxane backbone and dimethylvinylsilyl end groups located at both ends of the polysiloxane backbone. The polysiloxane backbone is formed by random copolymerization of dimethylsiloxane structural units, methyl(3,3,3-trifluoropropyl)siloxane structural units and methyloctylsiloxane structural units. Based on the total molar amount of the dimethylsiloxane structural unit, the methyl(3,3,3-trifluoropropyl)siloxane structural unit, and the methyloctylsiloxane structural unit being 100%, the content of the dimethylsiloxane structural unit is 40-90 mol%, the content of the methyl(3,3,3-trifluoropropyl)siloxane structural unit is 5-35 mol%, and the content of the methyloctylsiloxane structural unit is 5-25 mol%. The number-average molecular weight M of the siloxane terpolymer n The concentration ranges from 40,000 to 180,000 g / mol. The molecular weight distribution index of the siloxane terpolymer is in the range of 1.7 to 2.
4.
2. A method for preparing a siloxane terpolymer, wherein the method is for preparing the siloxane terpolymer as described in claim 1, comprising: A monomer mixture comprising octamethylcyclotetrasiloxane, 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and tetramethyltetraoctylcyclotetrasiloxane was prepared under inert gas protection and anhydrous conditions. The temperature of the monomer mixture is controlled to 50~65℃; A catalyst is added, and a ring-opening polymerization reaction is carried out to obtain a polymerization reaction solution; Tetramethyldivinyldisiloxane was added to the polymerization reaction solution to carry out an end-group capping reaction, resulting in a capped reaction solution. The end-capped reaction solution is cooled to obtain a cooled reaction solution; A quenching agent is added to the cooling reaction solution to perform a quenching treatment, resulting in a quenched reaction solution. The quenched reaction solution was washed with water until the aqueous phase was neutral, and the organic phase was then separated. The organic phase is subjected to depressurized removal of volatiles to obtain a siloxane terpolymer, wherein the siloxane terpolymer is an α,ω-divinyl-terminated poly(dimethylsiloxane-co-methyl(3,3,3-trifluoropropyl)siloxane-co-methyloctylsiloxane).
3. The method according to claim 2, wherein, The mass ratio of the octamethylcyclotetrasiloxane, the 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and the tetramethyltetraoctylcyclotetrasiloxane is 1:(0.12~1.84):(0.13~1.45), and the inert gas is nitrogen.
4. The method according to claim 2, wherein, The catalyst is anhydrous trifluoromethanesulfonic acid or a complex acid containing anhydrous trifluoromethanesulfonic acid, and the amount of catalyst added is 0.02% to 0.1% of the total mass of the octamethylcyclotetrasiloxane, the 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane and the tetramethyltetraoctylcyclotetrasiloxane.
5. The method according to claim 2, wherein, The amount of tetramethyldivinyldisiloxane added is 0.1% to 0.6% of the total mass of the octamethylcyclotetrasiloxane, the 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and the tetramethyltetraoctylcyclotetrasiloxane.
6. The method according to claim 2, wherein, The quenching agent is an aqueous solution of sodium bicarbonate, an aqueous solution of sodium carbonate, or ammonia.
7. The method according to claim 2, wherein, The depressurization removal of volatiles is carried out at 60~90℃ and a vacuum of -0.08~-0.095 MPa.
8. The method according to claim 2, wherein, The reaction time of the ring-opening polymerization reaction is in the range of 0.5 to 1 hour, and the reaction time of the end-capping reaction is in the range of 1 to 3 hours.